Study of ceramide glucosyltransferase - Narita, K; Narita, Keishi (2001)
﻿ Ceramide glucosyltransferase (CGT) is a key enzyme in glycosphingolipid (GSL) biosynthesis in eukaryotic cells. Inhibition of enzyme activity by an N-alkylated imino sugar, N-butyl-deoxynojirimycin (NB-DNJ), has been evaluated for the therapeutic treatment of inherited glycosphingolipid lysosomal storage diseases. To develop more selective drugs for potential clinical use, further investigation of possible side effects and the design of a more selective inhibitor is required. One concern for clinical use of NB-DNJ is the potential activation of CGT in vivo. When rats were treated with various concentrations of NB-DNJ for 13 weeks to assess the depletion of glycosphingolipids and up-regulation of CGT activity, the reduction of ganglioside levels was observed following an increase in NB-DNJ dose level up to 180 mg/kg/day. However, CGT activity levels were not significantly affected by NB-DNJ treatment. The lack of CGT up-regulation while reducing GSLs by NB-DNJ would be desirable in the clinic to avoid a rapid accumulation of GSLs if patient treatment was concluded. To aid in design of highly selective inhibitors for CGT, enzyme kinetic studies were performed using recombinant human CGT and five different imino sugars. The recombinant enzyme showed similar enzyme kinetics to a native enzyme from HL-60 cells. All the tested imino sugars showed a mixed-type inhibition for ceramide, and an increase in N-alkyl chain provided an improved uncompetitive inhibition. These data suggest that CGT may have two different sites for binding of imino sugars, and the N-alkyl chain length may affect the preference for binding site. When the protein sequence of CGT was analysed using www server programs to predict protein structure, a Rossman fold was predicted in the nucleotide-binding domain as observed in other nucleotide-sugar glycosyltransferase structures. Also, a significant folding similarity to bacterial glycosyltransferase SpsA was predicted. Based on these observations, a possible inhibitor-binding mechanism is discussed that may aid the design of highly selective inhibitors for CGT.